Development of E-Learning Modules to Improve Knowledge and Skills of The Taliabu Regional Language of High School Students - Rifkisyahputra, Rifkisyahputra; Ghufron, Anik (Jurnal Paedagogy, 2024)
This study aims to produce e-modules for the Taliabu regional language that are valid, practical, and effectively improve high school students’ knowledge and language skills. This study used research and development methods with the Borg & Gall model. This research was conducted at SMAN 3 Taliabu Island with a total of 71 subjects. Data collection techniques used interviews and tests. The data analysis technique used a paired sample t-test by carrying out analysis requirements in the form of the Kolmogorov-Smirnov normality test and homogeneity test. The expert test results showed that the Taliabu regional language e-Module was very feasible and practical for use by students and meets the criteria. The results of the Taliabu regional language e-module trial explained that there were differences in the level of knowledge and skills of students before and after using the e-module, this was proven by the results of the paired sample t-test which obtained a significance value (2-tailed) of 0.000 (p <0.05).